Hirokazu Miyazaki, “Arbitraging Japan. Dreams of Capitalism at the End of Finance”, University of California Press, Berkeley 2013 - Silvestri, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)